2017
DOI: 10.5194/cp-13-689-2017
|View full text |Cite
|
Sign up to set email alerts
|

A new high-resolution pollen sequence at Lake Van, Turkey: insights into penultimate interglacial–glacial climate change on vegetation history

Abstract: Abstract.A new detailed pollen and oxygen isotope record of the penultimate interglacial-glacial cycle, corresponding to the marine isotope stage (MIS) 7-6, has been generated from the Ahlat Ridge (AR) sediment core at Lake Van, Turkey. The presented Lake Van pollen record (ca. 250.2-128.8 ka) displays the highest temporal resolution in this region with a mean sampling interval of ∼ 540 years.The integration of all available proxies shows three temperate intervals of high effective soil moisture availability. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 77 publications
0
19
0
Order By: Relevance
“…Some pollen studies that have been conducted on Early to Middle Quaternary deposits (e.g., Shamb section-paleo-lake sediments in southern Armenia: [3]; North Caucasus and Kazakhstan: [65]) have suggested that the Pleistocene climate was characterized by an alternation of wet conditions during glacial periods and dry conditions during interglacial periods. Other, more modern pollen studies based on precise chronologies (Shamb section in southern Armenia: [5]; Dmanisi (Georgia): [66]; Lake Urmia (NW-Iran): [67]; Lake Van (Eastern Turkey): [68,69]) contradict this interpretation and suggest that glacial periods have been dry and cold and predominantly linked to a vegetation cover composed of grasses and herbs. In view of the high heterogeneity of hydrological conditions during glacial-interglacial cycles that must be expected for the mountainous Caucasus region, a comparison with these faraway paleoenvironmental archives will probably not lead to reliable statements.…”
Section: Deciduous Trees Refugia During Glacial Periodsmentioning
confidence: 99%
“…Some pollen studies that have been conducted on Early to Middle Quaternary deposits (e.g., Shamb section-paleo-lake sediments in southern Armenia: [3]; North Caucasus and Kazakhstan: [65]) have suggested that the Pleistocene climate was characterized by an alternation of wet conditions during glacial periods and dry conditions during interglacial periods. Other, more modern pollen studies based on precise chronologies (Shamb section in southern Armenia: [5]; Dmanisi (Georgia): [66]; Lake Urmia (NW-Iran): [67]; Lake Van (Eastern Turkey): [68,69]) contradict this interpretation and suggest that glacial periods have been dry and cold and predominantly linked to a vegetation cover composed of grasses and herbs. In view of the high heterogeneity of hydrological conditions during glacial-interglacial cycles that must be expected for the mountainous Caucasus region, a comparison with these faraway paleoenvironmental archives will probably not lead to reliable statements.…”
Section: Deciduous Trees Refugia During Glacial Periodsmentioning
confidence: 99%
“…Instead, it provides a unique opportunity for testing the envelope of environmental conditions assumed essential for dolomite formation. If juxtaposed with environmental proxies reflecting regional and local hydrological conditions (Kwiecien et al, ; Litt et al, ; North et al, ; Pickarski, Kwiecien, Djamali, et al, ; Pickarski, Kwiecien, Langgut, et al, ; Pickarski & Litt, ; Randlett et al, ; Stockhecke, Sturm, et al, ; Tomonaga et al, ) (Figure ), the dolomite occurrence is incompatible with the commonly accepted hypothesis of evaporitic conditions driving its formation. Our high‐resolution dolomite concentration data (Figure ), presented on the common Lake Van age model (Stockhecke, Kwiecien, et al, ), suggest that most of the dolomite‐rich intervals coincide with sediments deposited during a high lake level and generally wetter conditions.…”
Section: Introductionmentioning
confidence: 99%
“…(15) Lake Van in Turkey (Pickarski and Litt, 2017). The Mg/Ca-SSTs closely follow the runoff proxy, Ba/Ca values.…”
Section: Lake Level and Cave Records From The Northern Mediterranean mentioning
confidence: 78%